DISTANCE EDUCATION - A PRIORITY OF FIRE SAFETY TRAINING - Roziev Rustam Ruzimurodovich, (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the development of an information and educational environment that forms a culture of fire safety through continuous education based on these rules of fire safety, the organization of short-term training in distance form, and reveals the essence of the application of distance education in the field of fire safety. Visually-slide show, video explaining fires and their negative consequences, risk factors highlights the positive results in the formation of students ' fire safety culture and skills in the field of fire safety.